Mitochondrial networks in cardiac myocytes reveal dynamic coupling behavior - Kurz, Felix T. (Biophysical journal, 2015)
Oscillatory behavior of mitochondrial inner membrane potential (ΔΨm) is commonly observed in cells subjected to oxidative or metabolic stress. In cardiac myocytes, the activation of inner membrane pores by reactive oxygen species (ROS) is a major factor mediating intermitochondrial coupling, and ROS-induced ROS release has been shown to underlie propagated waves of ΔΨm depolarization as well as synchronized limit cycle oscillations of ΔΨm in the network. The functional impact of ΔΨm instability on cardiac electrophysiology, Ca2+ handling, and even cell survival, is strongly affected by the extent of such intermitochondrial coupling. Here, we employ a recently developed wavelet-based analytical approach to examine how different substrates affect mitochondrial coupling in cardiac cells, and we also determine the oscillatory coupling properties of mitochondria in ventricular cells in intact perfused hearts. The results show that the frequency of ΔΨm oscillations varies inversely with the size of the oscillating mitochondrial cluster, and depends on the strength of local intermitochondrial coupling. Time-varying coupling constants could be quantitatively determined by applying a stochastic phase model based on extension of the well-known Kuramoto model for networks of coupled oscillators. Cluster size-frequency relationships varied with different substrates, as did mitochondrial coupling constants, which were significantly larger for glucose (7.78 × 10−2 ± 0.98 × 10−2 s−1) and pyruvate (7.49 × 10−2 ± 1.65 × 10−2 s−1) than lactate (4.83 × 10−2 ± 1.25 × 10−2 s−1) or β-hydroxybutyrate (4.11 × 10−2 ± 0.62 × 10−2 s−1). The findings indicate that mitochondrial spatiotemporal coupling and oscillatory behavior is influenced by substrate selection, perhaps through differing effects on ROS/redox balance. In particular, glucose-perfusion generates strong intermitochondrial coupling and temporal oscillatory stability. Pathological changes in specific catabolic pathways, which are known to occur during the progression of cardiovascular disease, could therefore contribute to altered sensitivity of the mitochondrial network to oxidative stress and emergent ΔΨm instability, ultimately scaling to produce organ level dysfunction.